PENGARUH DISIPLIN KERJA, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT SIEMPAT NEMPU HULU, SIDIKALANG - Berga Simangunsong; Elperida J. Sinurat; Winarto Winarto (Jurnal Ilmu Manajemen METHONOMIX, 2022)
Performance is an important and interesting part because of its proven benefits, employee performance is the result of a complex process, and is influenced by factors originating from internal and external factors. Good employee performance is the hope of every company that employs these employees.In conducting the research, the authors examined the Office of the Head of the Siempat Nempu Hulu District, Sidikalang which is located at Jl. Sidikalang-Tigalingga, KM 11, Siempat Nempu Hulu, Dairi Regency, North Sumatra 22251 When the research was conducted in December 2020 until the study was completed. The population in this study which is used is the population as a whole (100%) because the number of employees in the Siempat Nempu Hulu District Head Office, Sidikalang is 30 people and it is less than 100 employees.The results showed the value of F count 27.656> F table 3.35 and the value of Sig is 0.000 <0.05, so work discipline, commitment, motivation together or simultaneously have a significant effect on employee performance. This is indicated by the coefficient of determination (R-Square) is 0.761. This value can be interpreted that the variables of work discipline, commitment, and motivation can affect employee performance by 76.1%, the remaining 100% - 76.1% = 23.9% is explained by other variables or factors.